Kemampuan Kolonisasi Cendawan Endofit dan Peningkatan Pertumbuhan Bibit Cabai - Evan Purnama Ramdan; Efi Toding Tondok; Suryo Wiyono; Sri Hendrastuti Hidayat; Widodo Widodo (UM Purwokerto Press, 2021)
Endophytic fungi are fungi that live in healthy plant tissues without causing disease symptoms. Endophytic fungi in chili have been tested as both biocontrol agents and growth promoters, but their colonization has not been reported. Therefore, this study aimed to determine the level of colonization of endophytic fungi and its effect on the growth of chili seedlings. A total of 8 endophytic fungi were prepared at a density of 2.8 × 106 CFU mL-1. Then the endophytic fungus was inoculated 2 times, first by soaking the seeds, and secondly by watering the endophytic fungus suspension on chili seedlings aged 3 weeks after sowing. Endophytic fungi were re-isolated on chili seedlings that were 4 weeks old after sowing on the roots and stems to determine their colonization ability. Chili seeds were then maintained for up to 4 weeks after transplanting to observe their growth. The results showed that the endophytic fungal colonization ranged from 26-60% on the chili root, while at the base of the stem it was 20-40% with a different pattern of colonization distribution. In addition, endophytic fungus colonization was also able to increase the shoot height and root length of chili seedlings.